More than Just Pneumonia: Acute Pulmonary Embolism in Two Middle-Aged Patients with COVID-19 - Jahinover Mazo; Sukhdev Singh; Zohaib Khan; Allison Foster; Ecaterina Komarnitsky; Abhiram Nagaraj; Soham Patel; Vinaya Kikkeri (Case Reports in Medicine)
Background. Although severe pneumonia and respiratory compromise have remained the predominant complications of coronavirus disease 19, we are now learning this virus is much more varied in its presentation. In particular, there are increasingly reported cases of thromboembolic events occurring in infected patients. Case Report. In this report, we present two patients, both under the age of 40 with known risk factors for venous thromboembolism, who presented with respiratory distress. Both patients were diagnosed with SARS-CoV-2 pneumonia and pulmonary embolism requiring management with anticoagulation. Both patients were discharged after a short course in the hospital. Conclusion. The discussion of a hypercoagulable state induced by coronavirus disease 19 has been well documented; however, the exact mechanisms remain unknown. We suspect that a prothrombotic inflammatory response provoked by coronavirus disease could be the culprit, acting as an additive effect on middle-aged patients with known risk factors for venous thromboembolism. We recommend clinicians closely monitor those with known risk factors for pulmonary embolism.